2014
DOI: 10.1002/glia.22625
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of GABA‐B Receptor in Schwann Cells Regulates Remak Bundles and Small Nociceptive C‐fibers

Abstract: The mechanisms regulating the differentiation into non-myelinating Schwann cells is not completely understood. Recent evidence indicates that GABA-B receptors may regulate myelination and nociception in the peripheral nervous system. GABA-B receptor total knock-out mice exhibit morphological and molecular changes in peripheral myelin. The number of small myelinated fibers is higher and associated with altered pain sensitivity. Herein, we analyzed whether these changes may be produced by a specific deletion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 74 publications
(125 reference statements)
2
44
0
Order By: Relevance
“…Although axonal cues are certainly critical, several studies suggest some genes controlling SC fate decision may act cell-autonomously within SCs [1315]. For example, SCs that have de-differentiated after injury can cell-autonomously upregulate Nrg1 to spur re-differentiation and remyelination [16].…”
Section: Rsc Fate Determinationmentioning
confidence: 99%
See 2 more Smart Citations
“…Although axonal cues are certainly critical, several studies suggest some genes controlling SC fate decision may act cell-autonomously within SCs [1315]. For example, SCs that have de-differentiated after injury can cell-autonomously upregulate Nrg1 to spur re-differentiation and remyelination [16].…”
Section: Rsc Fate Determinationmentioning
confidence: 99%
“…During development, the gamma-aminobutyric acid type B1 receptor (GABBR1) localizes primarily, albeit not exclusively, in RSCs rather than myelinating SCs [17]. Faroni et al deleted Gabbr1 in embryonic SCs and observed increased numbers of small diameter axons, although the axons were properly ensheathed, which correlated with an increase in the number of Remak bundles relative to controls as well as a corresponding decrease in the number of larger diameter axons [15]. Myelin protein levels were significantly increased, and the myelin was slightly thicker in Gabbr1 mutant nerves, however these measurements did take into consideration axonal diameter.…”
Section: Rsc Fate Determinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, given the synergic effects on locomotors activities, the activation of mixed central and peripheral targets by those molecules should not be excluded. However, very recent findings supported the hypothesis that GABA-B receptors may also control the nonmyelinating Schwann cells committed to ensheath the nociceptive fibers, strengthening a GABA-B role in the regulation of Schwann cell fate and nociceptive pathways in the PNS [37, 38]. …”
Section: Discussionmentioning
confidence: 99%
“…Very recently, Schwann cells were shown to express different isoforms of GABA-B receptor, such as −1a, −1b, and −2, which can participate in the control of the Schwann cell development and in the myelination process [35, 36]. The peripheral GABA-B receptors in Schwann cells may be involved in the regulation of the sensory and nociceptive functions [37, 38]. …”
Section: Introductionmentioning
confidence: 99%